3D model watermarking algorithm robust to geometric attacks. Issue 10 (14th September 2017) - Wang, Yinghui; Liu, Jing; Yang, Yajie; Ma, Douli; Liu, Ruijiao
Abstract : A 3D model watermarking method robust to geometric attacks is proposed. The vertices of the model are classified into three groups. The vertices of the low‐resolution group are used to establish an invariant space in which to resist geometric attacks. In the medium‐resolution group, appropriate vertices in which to embed the watermarking information are selected. The selection of vertices that contain information about the watermark is based on the area of the local set of the vertex, the curvature of which determines the embedding strength of the watermark. The vertices of the high‐resolution group are reserved for resisting simplification and smoothing attacks. The choice of the embedding position and the embedding strength can provide a suitable trade‐off between good transparency and maximum robustness of the proposed method. The simulation results show that, compared to existing state‐of‐the‐art methods, the proposed method is robust against attacks such as noise, smoothing, simplification, cropping, rotation, translation, and scaling while ensuring high visual quality of the watermarked model.